Serum Adiponectin Levels and Mortality after Kidney Transplantation - Alam, Ahsan (American Society of Nephrology, 2013)
BACKGROUND AND OBJECTIVES: Adiponectin (ADPN), an adipose tissue–derived hormone, has protective properties with respect to atherogenesis, inflammation, and energy homeostasis. Its beneficial role has not been consistent in patients with CKD or those undergoing dialysis. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This study examined the association of plasma ADPN levels in 987 prevalent kidney transplant recipients (mean age ± SD, 51.0±12.8 years; estimated GFR, 52.8±21.9 ml/min per 1.73 m(2); median time since transplant, 78 months) on all-cause mortality and death-censored graft failure. Patients were enrolled between February and August 2007 and were followed for a median of 51 months (interquartile range, 49–53 months). Using Cox proportional hazard models, the association of log-transformed plasma adiponectin was studied, with and without adjustment for demographic variables, baseline GFR, markers of inflammation, and cardiovascular risk factors. RESULTS: At baseline, patients in the lowest ADPN tertile were significantly more likely to be male; to be smokers; to have a higher baseline GFR, lower systolic BP, and lower HDL cholesterol level; and to have higher body mass index, abdominal circumference, C-reactive protein level, and total cholesterol level. The adjusted hazard ratio for death with elevated plasma ADPN (per natural log) was 1.44, and there was no significant interaction with any relevant cardiovascular risk subgroups (i.e., advanced age; diabetes; or elevated body mass index, waist circumference, C-reactive protein, or Framingham risk score). The hazard for death-censored graft failure was nonsignificant at 1.03. CONCLUSION: Elevated ADPN levels are associated with higher risk for death but not allograft failure in prevalent kidney transplant recipients.